Software Development and Crunch Time; and More. - Ortega, Ruben; Guzdial, Mark; Reed, Daniel (Communications of the ACM, 2010)
The article presents selected blogs from the journal's web site. Blog authors are identified and their blogs are presented. Google Inc. engineering director Ruben Ortega comments on the unavoidable nature of long hours spent in completing software development projects. Professor Mark Gudzial comments on open source software development and its effects on computing education. Daniel Reed, a vice president at Microsoft Corp., comments on the evolution of computing power, noting the applicability of Jevon's paradox regarding accelerated use of resources as they become more efficient to use.